REGISTRATION OF CUSTOMARY MARRIAGES IN SOUTH AFRICA: A CASE FOR MANDATORY REGISTRATION - Siyabonga Sibisi (Obiter, 2023)
Despite the enactment of the Recognition of Customary Marriages Act 120 of 1998 (the Recognition Act), many customary marriages remain unregistered. There are many reasons for non-registration. Since marriage certificates are associated with spousal benefits, people who do not expect such spousal benefits have no reason to register their marriage. These include the elderly and the widowed. The registration process is another reason for non-registration. Nevertheless, the difficulties that arise when a spouse does not have a registration certificate cannot be sustained. This article is motivation for mandatory registration of customary marriages. It briefly discusses the history of registration of customary marriages. It also studies the provisions of the Recognition Act in this regard. The difficulties that arise in the absence of a marriage certificate are also discussed. It recommends the use of traditional leaders, who receive a state salary, to facilitate the instantaneous registration of customary marriages. The benefits of involving traditional leaders are also discussed.